2017
DOI: 10.1038/bjc.2017.319
|View full text |Cite
|
Sign up to set email alerts
|

Ailanthone inhibits non-small cell lung cancer cell growth through repressing DNA replication via downregulating RPA1

Abstract: Background:The identification of bioactive compounds from Chinese medicine plays a crucial role in the development of novel reagents against non-small lung cancer (NSCLC).Methods:High throughput screening assay and analyses of cell growth, cell cycle, apoptosis, cDNA microarray, BrdU incorporation and gene expression were performed.Results:Ailanthone (Aila) suppressed NSCLC cell growth and colony formation in vitro and inhibited NSCLC tumour growth in subcutaneously xenografted and orthotopic lung tumour model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 25 publications
1
51
0
Order By: Relevance
“…Considering the potential acute and chronic effects of YTE‐17, the safety of YTE‐17 was also observed in AOM/DSS mice after gavaged with YTE‐17 for 12 weeks (Supporting Figure S5). Consistent with the results in the Ni's report, 54 no signs of damage of liver lobule and renal tubular epithelial cells in both group of the mice.…”
Section: Discussionsupporting
confidence: 92%
“…Considering the potential acute and chronic effects of YTE‐17, the safety of YTE‐17 was also observed in AOM/DSS mice after gavaged with YTE‐17 for 12 weeks (Supporting Figure S5). Consistent with the results in the Ni's report, 54 no signs of damage of liver lobule and renal tubular epithelial cells in both group of the mice.…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress-induced neuronal damage is critical for the development of ischemic stroke [1]. Ischemic stroke is a devastating disease and has been considered as the predominant cause of mortality and chronic disability worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
“…Macheret et al indicated that the enhancement of DNA replication is an important symbol of cancer progression ( 50 ). A recent study revealed that ailanthone can suppress NSCLC growth by restraining DNA replication through reducing RPA1 (replication protein A1) ( 51 ). In our research, the prediction signature was not only connected with the immune response but also with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%